The Effect of The In-Depth Learning Model and Learning Motivation On Accounting Comprehension, With Digital Literacy As A Moderating Variable - Ah Hisyam Ismail; Dhany Efita Sari (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to analyze the effect of deep learning models and learning motivation on the accounting comprehension of vocational high school students, as well as to examine the role of digital literacy as a moderating variable in this relationship. Deep learning is considered relevant because it emphasizes meaningful conceptual understanding through cognitive, reflective, and contextual engagement which is in line with the characteristics of accounting learning. This study uses a quantitative approach with an explanatory research design. Data were collected by distributing Likert scale questionnaires to students majoring in accounting in grades X, XI, and XII at vocational high schools. The sampling technique used proportionate stratified random sampling. The research instrument was developed based on indicators of deep learning, learning motivation, accounting comprehension, and digital literacy adapted from previous studies. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the direct influence and moderating effects between variables. The findings show that deep learning has a strong positive and significant effect on accounting comprehension (β = 0.506; p < 0.001), followed by learning motivation which also demonstrates a positive and significant influence (β = 0.288; p = 0.001). Digital literacy is found to have a positive direct effect on accounting comprehension (β = 0.181; p < 0.015). However, the moderating effects of digital literacy on the relationship between deep learning and accounting comprehension (p = 0.184) as well as learning motivation and accounting comprehension (p = 0.496) are not statistically significant, indicating that digital literacy does not strengthen these relationships. Collectively, the variables explain 80.2% (R² = 0.802) of the variance in accounting comprehension, highlighting the dominant role of deep learning and learning motivation in improving students understanding. Overall, the results emphasize the importance of implementing meaningful and reflective learning approaches alongside strengthening students learning motivation to enhance accounting comprehension. The findings also suggest that digital literacy plays a supportive role rather than a moderating factor in vocational accounting education